Can Transgression Define Identity in Educational Settings? A Basque-Based Framework for Identity-in-Interaction - Pérez-Izaguirre, Elizabeth (Frontiers in Psychology, 2019)
Interaction in educational environments might refer to a set of relationships between individuals in a school system. These links can be considered within a power-relations framework that includes the role of each of the subjects in a school and its community. This paper focuses on "transgressive" interactions involving adolescent students from diverse ethnic backgrounds in a Basque secondary school and relies on the concept of identity-in-interaction from a sociocultural approach, according to which, identity is constituted in a process of exchange between two or more parties. This research is drawn from the results of an ethnographic study conducted between July 2015 and June 2016 in a Basque secondary school attended by a high proportion of immigrant students, which shares characteristics with the broader Basque educational context. The methods used to collect data included documentary analysis, nine-months of participant observation, 36 in-depth interviews, and four focus groups. Transgression in this context refers to the act of questioning socially established limits of behavior, which is considered typical during adolescent years. I categorize three types of student interaction as transgressive: personal, civic, and social limit transgressions, which involve challenges to peer-interpersonal, institutional, and community rules of interaction, respectively. In the Basque Country there are two official languages, Basque and Spanish, and students are instructed in both languages. They must daily face the particularities of a bilingual society where Basque is still a minority language. Community transgression is noteworthy, as immigrant students resisted the rule enforcing Basque instruction, leading to intercultural conflict with teachers. The study argues that identity can be constructed through transgression: immigrants’ refusing to learn Basque is a matter of rebellion that acts as an identity marker. This study contributes to the discussion of identity-in-interaction. Based on empirical data it uses the framework of transgression in multi-ethnic educational environments to consider community languages in a broader power-relations framework.